2016
DOI: 10.1038/mtm.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real-time imaging system for hypoxic cell apoptosis

Abstract: Hypoxic regions within the tumor form due to imbalances between cell proliferation and angiogenesis; specifically, temporary closure or a reduced flow due to abnormal vasculature. They create environments where cancer cells acquire resistance to therapies. Therefore, the development of therapeutic approaches targeting the hypoxic cells is one of the most crucial challenges for cancer regression. Screening potential candidates for effective diagnostic modalities even under a hypoxic environment would be an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…A strong correlation for both hypoxic (r=0.992) and normoxic (r=0.991) conditions is observed on tumor volume. Also as seen in Figure 2 in hypoxia which could be defined as 10% O 2 of normoxia [18] apoptic region is considerably larger and tumor shows migrative behavior which is also in line with experimental results [19,20]. In the figure, Many studies have shown that glucose is an important factor in tumor growth.…”
Section: Consistencysupporting
confidence: 84%
“…A strong correlation for both hypoxic (r=0.992) and normoxic (r=0.991) conditions is observed on tumor volume. Also as seen in Figure 2 in hypoxia which could be defined as 10% O 2 of normoxia [18] apoptic region is considerably larger and tumor shows migrative behavior which is also in line with experimental results [19,20]. In the figure, Many studies have shown that glucose is an important factor in tumor growth.…”
Section: Consistencysupporting
confidence: 84%
“…Also as seen in Figure 6, under hypoxia, which could be defined as 10% O 2 of normoxia (37), the apoptotic region is considerably larger and tumor shows migratory behavior. This phenomenon can be observed in experimental studies (38,39). 8.…”
Section: Consistencymentioning
confidence: 55%
“…Furthermore, we devised this system to only work in a hypoxic environment so that it can be utilized for screening anticancer drugs targeting cancer stem cells, since they tend to reside in hypoxic regions. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we devised this system to only work in a hypoxic environment so that it can be utilized for screening anticancer drugs targeting cancer stem cells, since they tend to reside in hypoxic regions. 15 In radiation therapy, a major component of cancer therapy (along with surgery and chemotherapy), the frequency at which apoptosis is induced in tumors is known to be as low as several percent, regardless of the p53 status. 16 In addition, radiation not only directly causes necrosis in tumor cells but also causes tumor vascular damage, resulting in secondary necrosis in tumor cells via oxygen and nutrient depletion.…”
Section: Introductionmentioning
confidence: 99%